2018
DOI: 10.1371/journal.pone.0209047
|View full text |Cite|
|
Sign up to set email alerts
|

Origanum vulgare terpenoids modulate Myrmica scabrinodis brain biogenic amines and ant behaviour

Abstract: Coordinated social behaviour is fundamental for ant ecological success. However, even distantly-related organisms, such as plants, have evolved the ability to manipulate ant collective performances to their own advantage. In the parasitic system encompassing Maculinea butterflies, Myrmica ants, and Origanum vulgare plants, the ant-plant interaction elicits the release of a volatile terpenoid compound (carvacrol) which is used by the gravid butterfly to locate the ideal oviposition site. Here we show that this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…Very recently, it has been shown that this antplant interaction could be maintained through manipulation signals. Mixtures of carvacrol and thymol decrease Myrmica ant movements and increase their aggressive behaviors acting on the brain levels of biogenic amines (Mannino et al, 2018). Therefore, similarly to the scenario described by Hojo et al (2015) (for further details see below), here oregano seems to manipulate Myrmica ants by volatile cues in order to increase partner fidelity and obtain protection against herbivores by patrolling workers.…”
Section: Signals Used During Butterfly Ovipositionmentioning
confidence: 71%
See 1 more Smart Citation
“…Very recently, it has been shown that this antplant interaction could be maintained through manipulation signals. Mixtures of carvacrol and thymol decrease Myrmica ant movements and increase their aggressive behaviors acting on the brain levels of biogenic amines (Mannino et al, 2018). Therefore, similarly to the scenario described by Hojo et al (2015) (for further details see below), here oregano seems to manipulate Myrmica ants by volatile cues in order to increase partner fidelity and obtain protection against herbivores by patrolling workers.…”
Section: Signals Used During Butterfly Ovipositionmentioning
confidence: 71%
“…Using a multidisciplinary approach, authors shed light on the indirect mechanism used by M. arion females to detect the presence of the Myrmica ants by means of a very tiny variation in the LHP volatilome (Patricelli et al, 2015) and on the way a certain degree of overlap between the two butterfly resources, LHPs and Myrmica ants, can be maintained (Mannino et al, 2018).…”
Section: Signals Used During Butterfly Ovipositionmentioning
confidence: 99%
“…Increasing walking speed could not only increase foraging efficiency but also cause greater energy expenditure by the colony. Mannino et al [55] also found an increase in the walking activity of the ants Formica cinerea, Tetramorium caespitum, and Myrmica scabrinodis, when exposed to thymol and carvacrol, as well as an increase in the levels of dopamine and tyramine in the brain of these ants, which is associated with their locomotion.…”
Section: Discussionmentioning
confidence: 90%
“…These amines may be related to the different behavior of ants since they have high metabolic diversity and act as neuromodulators and neurotransmitters [52][53][54]. Recent studies already demonstrate, for example, that thymol and its isomer carvacrol interfere with the level of dopamine and tyramine in ant brains, which is associated with their locomotion, as well as their aggressive behavior [55].…”
Section: Discussionmentioning
confidence: 99%
“…BAs are nitrogen compounds with one (or more) amine groups originating from the decarboxylation of amino acids. An amazing diversity of BAs has been described, with some compounds acting as toxins, while only a few playing a significant physiological role, which differs between vertebrates and invertebrates [20,23,24].…”
Section: Introduction and Outlinesmentioning
confidence: 99%